2017
DOI: 10.1093/cid/cix734
|View full text |Cite
|
Sign up to set email alerts
|

Dual Therapy With Darunavir and Ritonavir Plus Lamivudine vs Triple Therapy With Darunavir and Ritonavir Plus Tenofovir Disoproxil Fumarate and Emtricitabine or Abacavir and Lamivudine for Maintenance of Human Immunodeficiency Virus Type 1 Viral Suppression: Randomized, Open-Label, Noninferiority DUAL-GESIDA 8014-RIS-EST45 Trial

Abstract: NCT02159599.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 14 publications
2
58
1
2
Order By: Relevance
“…Some low/middle-income countries have used generic ART formulations to address the cost challenge [10,11]. Others have explored whether monotherapy or dual therapy can be used safely to reduce costs [12][13][14][15]. Strategic use of newly available generic antiretroviral (ARV) drugs has now entered the cost discussion in high-income countries, with modelling studies projecting significant savings from any increased use of generic ART [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Some low/middle-income countries have used generic ART formulations to address the cost challenge [10,11]. Others have explored whether monotherapy or dual therapy can be used safely to reduce costs [12][13][14][15]. Strategic use of newly available generic antiretroviral (ARV) drugs has now entered the cost discussion in high-income countries, with modelling studies projecting significant savings from any increased use of generic ART [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…3TC regimens have consistently met noninferiority, evidenced in both simplification from a previous ATV/r-based regimen and switching from a variety of PI and NNRTI-based 3DRs (ATLAS-M, SALT) [29,32,33]. There is limited evidence studying DRV in this population, although results from the DUAL-GESIDA study are promising [30]. These studies have not been associated with treatment-emergent resistance and have similar rates of viral suppression to comparator 3DRs.…”
Section: Discussionmentioning
confidence: 99%
“…Seven non-inferiority studies of NRTI-inclusive 2DRs in treatment-experienced populations were identified ( Table 2) [27][28][29][30][31][32][33][34]. The COOL study evaluating EFV ?…”
Section: Nrti Inclusivementioning
confidence: 99%
See 1 more Smart Citation
“…This finding was not observed in a randomized study comparing the same dual regimen vs . standard triple therapy , because randomized studies were performed in selected patients, without prior toxicity and with a short duration of previous therapy, and are therefore not representative of this indication in real‐life settings. With this limitation, the findings suggest that dual therapies are promising strategies, and our data confirm that they could help to reduce renal toxicity, to a similar or greater extent compared with switching from TDF to abacavir, because these patients had worse baseline characteristics, a longer duration of HIV infection and TDF use, and more previous lines of cART.…”
Section: Discussionmentioning
confidence: 99%